Network democracy : conservative politics and the violence of the liberal age - Giesbrecht, Jared, 1979- (Montreal ; Kingston ; London ; Chicago : McGill-Queen's University Press, 2017)
A unique hybrid of ancient and contemporary conservative thought that offers a radical challenge to Western liberalism.
Network patternings -- Violence and domination -- Protocolic modulations -- The logic of liberalism -- Legitimizing violence -- Conservative democracy.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 06, 2025).
eBooks on EBSCOhost
Keywords: Democracy; Conservatism; Liberalism; Violence; Time pressure; Free enterprise; Violence; Conservatisme; Libéralisme.; Violence; Contrainte de temps; conservatism; liberalism; violence; POLITICAL SCIENCE -- General; Free enterprise; Conservatism; Democracy; Liberalism; Time pressure; Violence